Development of Incident Response Playbooks and Runbooks for Amazon Web Services Ransomware Scenarios - Gandini, Samuele (My University, 2023)
In today’s digital landscape, enterprises encounter myriad cybersecurity challenges that jeopardize their critical digital assets. Modern cyber threats have evolved drastically, adapting to the proliferation of cloud technologies that drive organizations towards platforms like AWS that offer convenience, cost-reduction, and reliability. However, this transition introduces new security risks because threat actors are motivated to craft and deploy advanced malware explicitly targeting the cloud. Ransomware emerged as one of the most impactful and dangerous cyber threats, still in 2023, encrypting data and demanding payment (usually in untraceable tokens) for the decryption key. Confidentiality, integrity, and availability of cloud assets stand perpetually vulnerable, and sometimes, unprepared businesses suddenly hit by ransomware cannot find a way out. Besides financial loss and operation disruption, the breach of sensitive information compromises trust, leading to reputational damage that's hard to mend. Corporations are urged to develop robust defensive strategies to identify, contain, and recover from ransomware and other cloud threat exploitation. Traditional cybersecurity approaches must rapidly reshape to manage emerging menaces. Hence, they require new specialized and well-structured incident response plans to become the bedrock of the security tactics. This thesis dives into the complexities of designing and implementing accurate incident response Playbooks and Runbooks, focusing on handling the common danger of ransomware, especially within Amazon Web Services (AWS). This research journey is strictly connected to the real-world context, resulting from a six-month internship within Bynder, a digital asset management leader company. This experience culminated in conceptualizing the step-by-step procedures against ransomware incidents in cloud infrastructures, improving communication, and coordinating actions during high-pressure situations.
Keywords: Cybersecurity, Incident Response, Cloud Computing, Ransomware, Amazon Web Services (AWS), Cloud Security, Playbooks, Runbooks, proactive strategies